2021
DOI: 10.2147/cmar.s314369
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Complement Component 1q Levels in Predicting the Efficacy of Combined Immunotherapy in Patients with Lung Cancer

Abstract: Objective To evaluate the value of serum complement component 1q (C1q) levels in predicting the efficacy of combined immunotherapy in patients with lung cancer. Methods A total of 42 patients with lung cancer who received combined immunotherapy in the cancer center of Renmin Hospital of Wuhan University were included in this study. The clinical data of serum C1q and lactate dehydrogenase (LDH) levels before and three weeks after immunotherapy were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Other proteomic studies have identified C1q as a potential prognostic indicator. In lung and kidney cancer and in glioma, higher C1q levels are associated with a negative prognosis [25,26]. Conversely, in breast cancer and some types of lung cancer, as with our study, higher C1q levels are associated with a more positive prognosis [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…Other proteomic studies have identified C1q as a potential prognostic indicator. In lung and kidney cancer and in glioma, higher C1q levels are associated with a negative prognosis [25,26]. Conversely, in breast cancer and some types of lung cancer, as with our study, higher C1q levels are associated with a more positive prognosis [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…( 51 ) suggested combining DNA and RNA sequencing, immunohistochemical staining results, demographic baseline data, medical history, and laboratory test results to analyze the information related to efficacy and break the limitation of relying only on PD-1 expression level and TMB level to predict immunotherapy response, and develop a mature model for immunotherapy response prediction for Chinese lung cancer patients. Along with PD-L1 expression, TMB, and TIL, it has been demonstrated that miRNA abnormalities ( 62 ), EGFR mutations ( 54 ), TP53 mutations ( 63 ), ALK rearrangements ( 55 ), gut microbiota ( 56 ), Fc gamma receptor (FcγR) polymorphisms ( 57 ) and serum complement levels ( 58 ) all influence immunotherapy response to some extent. It would facilitate the robustness of prediction if this information could be merged with pathological sections and imaging histology to form multi-omics integrated data.…”
Section: The Existing Approaches To Predicting Immunotherapy Outcomesmentioning
confidence: 99%
“…However, identifying the patient cohort that will benefit from immunotherapy remains a pressing problem to be addressed. Previous studies have explored the prediction of immunotherapy efficacy from multiple perspectives, such as drug-based score ( 12 ), lung immune prognostic index (LIPI) ( 13 ), smoking ( 14 ), liver metastasis ( 15 ), lactate dehydrogenase (LDH) ( 16 , 17 ), tumor mutational burden (TMB) expression ( 18 ), neutrophil-to-lymphocyte ratio (NLR) ( 19 , 20 ), modified lung immune predictive index (mLIPI) scores ( 21 ), and so on. Despite achieving some results, the existing literature does not completely solve the problem of predicting immunotherapy efficacy.…”
Section: Introductionmentioning
confidence: 99%